EFFECTIVENESS OF KWL-PLUS MODEL ON ACHIEVEMENT IN CHEMISTRY OF SECONDARY SCHOOL STUDENTS - Rachana V and Prasida (PEDAGOGICS: A Journal from School of Pedagogical Sciences, 2017)
KWL-Plus is designed as a model used to develop comprehension by helping students to create a connection between their prior knowledge and what they hear or view. KWL requires students to identify what is known about a particular subject (K), what the students wants to know (W), and what is learned (L). KWL Plus adds mapping and summarization (Carr, E and D, Ogle, 2010). The present study was aimed at finding the effectiveness of KWL-Plus model on achievement in chemistry of Standard VIII students. A true experimental method was used to investigate the present study. A sample of 80 students was selected randomly for the study.40 students were randomly selected to form an experimental group and another 40 students were randomly selected for Control group. The experimental group were taught through KWL Plus model and the control group were taught by the existing method of teaching. The data were collected and analysed using appropriate statistical techniques. On the basis of analysis, a significant difference was found between the mean scores for achievement of experimental and control group. The result shows that KWL Plus model was more effective than the existing method in secondary school students.